Two Novel Palbociclib-Resorcinol and Palbociclib-Orcinol Cocrystals with Enhanced Solubility and Dissolution Rate - Chenxin Duan; Wenwen Liu; Yunwen Tao; Feifei Liang; Yanming Chen; Xinyi Xiao; Guisen Zhang; Yin Chen; Chao Hao (MDPI AG, 2021)
Palbociclib (PAL) is an effective anti-breast cancer drug, but its use has been partly restricted due to poor bioavailability (resulting from extremely low water solubility) and serious adverse reactions. In this study, two cocrystals of PAL with resorcinol (RES) or orcinol (ORC) were prepared by evaporation crystallization to enhance their solubility. The cocrystals were characterized by single crystal X-ray diffraction, Hirshfeld surface analysis, powder X-ray diffraction, differential scanning calorimetry, thermogravimetric analysis, Fourier transform infrared and scanning electron microscopy. The intrinsic dissolution rates of the PAL cocrystals were determined in three different dissolution media (pH 1.0, pH 4.5 and pH 6.8), and both cocrystals showed improved dissolution rates at pH 1.0 and pH 6.8 in comparison to the parent drug. In addition, the cocrystals increased the solubility of PAL at pH 6.8 by 2-3 times and showed good stabilities in both the accelerated stability testing and stress testing. The PAL-RES cocrystal also exhibited an improved relative bioavailability (1.24 times) than PAL in vivo pharmacokinetics in rats. Moreover, the in vitro cytotoxicity assay of PAL-RES showed an increased IC50 value for normal cells, suggesting a better biosafety profile than PAL. Co-crystallization may represent a promising strategy for improving the physicochemical properties of PAL with better pharmacokinetics.